Performance analysis : Jan 1983 - Aug 1998. - Ghin, Margaret Ser Chi. (2008)
The period of interest was for the fifteen years from Jan 1983 to August 1998. The performance of the four sectors namely, SES All-Industrial and Commerce, SES All-Finance, SES All-Hotel and SES All-Property were examined.